CBMIR_SMEr: An Effective Multi-Domain Content-Based Image Retrieval Method with Feature Selection for Colorectal Histopathological Images - Muzoglu, Nedim (Fırat University, 2026)
Histopathological images used in colorectal cancer diagnosis can enhance the efficiency of clinical processes when supported by content-based medical image retrieval (CBMIR) systems. In this study, a method called CBMIR_SMEr, based on low-parameter and computationally efficient deep learning architectures, is proposed. The method was applied to the EBHI-Seg dataset as a CBMIR approach for histopathological colorectal images. Features extracted from ShuffleNet, MobileNetV2, and EfficientNet-B0 architectures were combined, and the most discriminative features were selected using the ReliefF algorithm. Image similarities were calculated using Euclidean and Cosine distance metrics. On the EBHI-Seg dataset, using the Cosine similarity, mAP@5 = 0.9511 and Precision@5 = 0.9141 were achieved for 800 features, while using Euclidean similarity, mAP@5 = 0.9353 (for 800 features) and Precision@5 = 0.9109 (for 600 features) were obtained. To evaluate the robustness of the method, experiments were also conducted on the UC Merced dataset, where Euclidean similarity achieved mAP@5 = 0.9461 (600 features) and Precision@5 = 0.9259 (800 features), while Cosine similarity achieved mAP@5 = 0.9577 (600 features) and Precision@5 = 0.9340 (800 features). These results represent the highest retrieval performance obtained on both datasets. Experimental findings demonstrate that the proposed CBMIR_SMEr method performs with high accuracy and stability on both histopathological and general image datasets, contributing as one of the first CBMIR-based approaches in colorectal image analysis.

Kolorektal kanser tanısında kullanılan histopatolojik görüntüler, içerik tabanlı medikal görüntü geri getirme (CBMIR) sistemleriyle desteklenerek klinik süreçlerin etkinliğini artırabilir. Bu çalışmada, düşük parametreli ve hesaplama açısından verimli derin öğrenme mimarilerine dayanan CBMIR_SMEr adlı bir yöntem önerilmektedir. Yöntem, histopatolojik kolorektal görüntülere yönelik bir CBMIR yaklaşımı olarak EBHI-Seg veri seti üzerinde uygulanmıştır. ShuffleNet, MobileNetV2 ve EfficientNet-B0 mimarilerinden çıkarılan öznitelikler birleştirilmiş, ardından ReliefF algoritmasıyla en ayırt edici öznitelikler seçilmiştir. Görüntü benzerlikleri Öklidyen (Euclidean) ve Kosinüs (Cosine) ölçüm yöntemleriyle hesaplanmıştır. EBHI-Seg veri seti üzerinde, Kosinüs benzerliği kullanıldığında 800 öznitelik için mAP@5 = 0.9511 ve Precision@5 = 0.9141, Öklidyen benzerliği kullanıldığında ise 800 öznitelik için mAP@5 = 0.9353 ve 600 öznitelik için Precision@5 = 0.9109 değerleri elde edilmiştir. Yöntemin kararlılığı UC Merced görüntü veri kümesi üzerinde test edilmiş, Öklidyen benzerliği ile 600 öznitelikte mAP@5 = 0.9461 ve 800 öznitelikte Precision@5 = 0.9259, Kosinüs benzerliği ile 600 öznitelikte mAP@5 = 0.9577 ve 800 öznitelikte Precision@5 = 0.9340 değerleri elde edilmiştir. Bu sonuçlar, her iki veri kümesi için de elde edilen en yüksek geri getirme performanslarını göstermektedir. Deneysel bulgular, önerilen CBMIR_SMEr yönteminin hem histopatolojik hem de genel görüntü veri kümelerinde yüksek doğruluk ve kararlılıkla çalıştığını ortaya koymakta ve kolorektal görüntü analizi alanında literatüre önemli bir katkı sağlamaktadır.
CBMIR_SMEr: Kolorektal Histopatolojik Görüntüler için Öznitelik Seçimi Destekli ve Çok Alanlı İçerik Tabanlı Görüntü Geri Getirme Yaklaşımı
Keywords: Evolutionary Computation; Evrimsel Hesaplama